PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PADA SUBSEKTOR APPAREL AND LUXURY GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2023 - Dela Puspitasari; Ratna Dumilah (Accounting Journal of Ibrahimy (AJI), 2026)
This study aims to investigate the influence of Current Ratio (CR) and Debt to Equity Ratio (DER) on financial distress. Utilizing a quantitative, descriptive associative method, the research collected 30 sample data from 6 purposively selected companies within the Apparel and Luxury Goods subsector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period, drawn from a total population of 22 companies. Hypothesis testing was performed using panel data regression analysis with E-Views 12 software and a 5% confidence level. The findings indicate that CR and DER collectively influence financial distress (F-calculated 47.777715 > F-table 3.35, significance 0.000000 < 0.05), with an Adjusted R-squared of 91.68%, while the remaining 8.32% is influenced by other unexamined variables. Partially, CR shows a positive and significant influence (t-calculated 2.382174 > t-table, significance 0.0263 < 0.05), whereas DER exhibits a negative but not significant influence (t-calculated 0.891224 < t-table 2.051, significance 0.3825 > 0.05) on financial distress.